Study on Physical Simulation Test of Unloading Mechanism of River Valley Down-cutting in a Hydropower Station - HE Shutao; DENG Hui; WU Xiaojun; XIAO Yuyue; SU Hang (Renmin Zhujiang)
In order to study the unloading mechanism of river valley down-cutting in a hydropower station, according to the similarity theory, this paper carries out the indoor physical simulation tests with matching similar materials and building models to simulate the river valley down-cutting for 5 times, and the stress analysis, displacement analysis and failure analysis of rock mass. The results show that during the unloading process, the stress of the slope on both sides decreases gradually, cracks appear on partial slope surface, collapse occurs in a small scale, and the slope displaces towards the river valley.